Evaluating quality and reliability of final examination questions for MAT0144 using rasch model - Bahrom, Suhaila; Mat Yaacob, Siti Nubailah; Happas, A'fifah; Saidin, Nurhafizah; Mat Nawi, Mohd Nazim (CFS, IIUM, 2022)
The construction of the final examination questions based on the proper guideline such as according to course learning outcomes (CLO) will help in measuring students’ abilities based on comprehensive cognitive skills. A well-constructed question on the final examination should be suitable for the intended level of knowledge. In this study, the results from final examination Statistics, MAT0144 taken by Biological Module students in Semester 3, 2021/2022 were analysed using the Rasch Model. It is a process of statistically examining both the test questions and the students’ answer to evaluate the quality and reliability of the test item and the examination paper as a whole. The examination paper items were examined, and the ones which did not meet expectations were identified. The best test item distinguishes between students who do well on the exam and those who do not. Item difficulty on the equal interval scale (logit) must be maintained regardless of the ability of the students who challenge the item. The overall quality and reliability of the examination questions constructed were relatively good, calibrated with the students' learned ability, and appropriate for the intended students, according to the analysis.